The Pm5e Gene Has No Negative Effect on Wheat Agronomic Performance: Evidence From Newly Established Near-Isogenic Lines - Qiu, Dan; Huang, Jiang; Guo, Guanghao; Hu, Jinghuang; Li, Yahui; Zhang, Hongjun; Liu, Hongwei; Yang, Li; Zhou, Yang; Yang, Benzhou; Zhang, Yudan; Liu, Zhiyong; et al. (Frontiers in Plant Science, 2022)
Wheat genotypes resistant to powdery mildew (Blumeria graminis f. sp. tritici, Bgt) provide a sustainable means for the disease control. We developed a pair of near-isogenic lines H962R and H962S with contrasting reactions to powdery mildew from a residue heterozygous line. H962R was resistant to most of the 135 Bgt isolates collected from the major wheat producing regions of China and showed a similar virulence/avirulence pattern as Fuzhuang 30, Xiaobaidong, and Hongquanmang carrying resistance allele of Pm5e, but H962S was resistant to none of them. A dominant gene was responsible for the powdery mildew resistance of H962R as revealed by the genetic analysis using segregating populations derived from a cross between H962R and H962S. Molecular marker analysis detected a resistance locus, designated PmH962, on a region of chromosome 7BL where Pm5e resides. This locus was co-segregated with the functional marker of Pm5e. The PCR-based sequence alignment of Pm5e demonstrated that H962R had an identical sequence as Fuzhuang 30 (haplotype HapGA), and H962S possessed the same sequence as the powdery mildew susceptible cultivar Kenong 199 (haplotype HapGG). The genomic compositions of lines H962R and H962S were highly comparable as evidenced by only a small percentage of SNP variations detected by the 16K Genotyping by Target Sequencing (GBTS) SNP array and the 90K Illumina iSelect Wheat SNP array. The two lines performed similar in the yield related and plant growth traits investigated, except for greater kernel weight in H962R than H962S. This indicates that Pm5e has no yield penalty and can be serves as an excellent disease resistance gene in wheat breeding.